Survey of transcripts in the adult Drosophila brain. - Posey, K.L.; Jones, L.B.; Cerda, R.; Bajaj, M.; Huynh, T.; Hardin, P.E.; Hardin, S.H. (Genome Biology, 2001)
Classic methods of identifying genes involved in neural function include the laborious process of behavioral screening of mutagenized flies and then rescreening candidate lines for pleiotropic effects due to developmental defects. To accelerate the molecular analysis of brain function in Drosophila we constructed a cDNA library exclusively from adult brains. Our goal was to begin to develop a catalog of transcripts expressed in the brain. These transcripts are expected to contain a higher proportion of clones that are involved in neuronal function.The library contains approximately 6.75 million independent clones. From our initial characterization of 271 randomly chosen clones, we expect that approximately 11% of the clones in this library will identify transcribed sequences not found in expressed sequence tag databases. Furthermore, 15% of these 271 clones are not among the 13,601 predicted Drosophila genes.Our analysis of this unique Drosophila brain library suggests that the number of genes may be underestimated in this organism. This work complements the Drosophila genome project by providing information that facilitates more complete annotation of the genomic sequence. This library should be a useful resource that will help in determining how basic brain functions operate at the molecular level.